2019
DOI: 10.14581/jer.19004
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Etiological Profile of Pediatric Refractory Status Epilepticus at a Public Hospital in India

Abstract: Background and Purpose Refractory status epilepticus (RSE) has been infrequently studied in Indian children. This research was conducted to study the clinico-etiological profiles and short-term outcomes of children aged 1 month to 12 years with convulsive RSE, at a public hospital. Methods The study was conducted between 1st April 2016 and 28th February 2017 after receiving clearance from an Institutional Ethics Committee. All children (aged 1 month to 12 years) who pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The mortality rate in the present study was similar to other Indian studies [21,22], whereas studies from developed countries reported comparatively less mortality (9-24%) [23,24]. The risk factors for mortality in the present study included longer duration of SE, acute symptomatic etiology, delay in receiving first AED, RSE, the requirement of ventilator support, and circulatory impairment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mortality rate in the present study was similar to other Indian studies [21,22], whereas studies from developed countries reported comparatively less mortality (9-24%) [23,24]. The risk factors for mortality in the present study included longer duration of SE, acute symptomatic etiology, delay in receiving first AED, RSE, the requirement of ventilator support, and circulatory impairment.…”
Section: Discussionsupporting
confidence: 87%
“…We have found that acute causes of SE trend toward the worse outcome. Duration of SE is the only potentially modifiable determinant of mortality [21]. Therefore, besides improvisation of peripheral institutes in critical care, need for high-end ambulances to transport children with SE should be the futuristic goal of the government.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities were detected in 22.5% but none required surgical intervention. In the study by Sadik et al, 72% of the patients underwent neuroimaging, with abnormalities detected in 22.8% of them (54) . In the series of Şahin et al, 20 of 45 convulsive patients underwent CT imaging, and 55% had abnormalities, while 23 patients were examined using cranial MRI, with pathological findings detected in 78.2% of them (55) .…”
Section: Discussionmentioning
confidence: 99%
“…SE has significant morbidity and mortality (29%), which is influenced majorly by the etiology and the management. Given the lack of information on etiology and outcome of SE in children from India, the study by Chetan, et al [2] in this issue of Indian Pediatrics is a welcome addition to the literature on the topic [3,4].…”
Section: E D I T O R I a L E D I T O R I A L E D I T O R I A L E D I mentioning
confidence: 99%